1994
DOI: 10.1159/000217107
|View full text |Cite
|
Sign up to set email alerts
|

Time-Dependent Changes in Platelet Aggregation, Fibrinolytic Activity, and Peripheral Serotonergic Measures in Rats Subjected to Water Immersion Restraint Stress

Abstract: The effects of water immersion restraint stress on collagen-induced platelet aggregation in whole blood, and on the fibrinolytic and serotonergic systems in rats have been studied. One hour long stress caused a release of tissue plasminogen activator (tPA) into the blood and a shortening of euglobulin clot lysis time (ECLT), whereas restraint of longer duration was responsible for a reduction in platelet aggregation, an elevation in the activity of plasminogen activator inhibitor with a concomitant fall in tPA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 12 publications
0
4
0
Order By: Relevance
“…The serotonergic system, with neurons in the dorsal raphe nucleus projecting throughout the forebrain and neocortex, has long been known for its effects on mood and various psychiatric conditions, and is also responsive to stress [83]. However, recent research is revealing that the serotonergic system and its interaction with other neurotransmitter systems serve important cognitive roles as well.…”
Section: Other Systemsmentioning
confidence: 99%
“…The serotonergic system, with neurons in the dorsal raphe nucleus projecting throughout the forebrain and neocortex, has long been known for its effects on mood and various psychiatric conditions, and is also responsive to stress [83]. However, recent research is revealing that the serotonergic system and its interaction with other neurotransmitter systems serve important cognitive roles as well.…”
Section: Other Systemsmentioning
confidence: 99%
“…While some studies have shown that platelet function increases response to acute stress (von Känel and Dimsdale 2000), it has been reported that it has no significant effect on platelet aggregation in mice (Matsuhisa et al 2014). It has been shown that acute stress (water immersion restraint and cold restraint) in rats may cause a decrease in platelet aggregation (Malyszko et al 1994, Takeda et al 1992. In dogs under anesthesia, acute hypothermia led to transient platelet hypoaggregability (Yoshihara et al 1985).…”
Section: Discussionmentioning
confidence: 99%
“…These inconsistencies may result from numerous study variations, including stress levels and platelet aggregation measuring techniques. In the literature, the effects of different stress protocols (repeated cold stress, acute vital stress, immobilization stress, water immersion stress, restraint stress, cold stress) on platelet functions have been investigated in previous rat and mouse stress studies (Bondarchuk et al 2020, Hata et al 1992, Hatu et al 1991, Kawabata and Hata 1993, Loban'-Chereda and Novosel'tseva 1990, Malyszko et al 1994, Pethaperumal et al 2022, Takeda et al 1992.…”
Section: Introductionmentioning
confidence: 99%
“…The study of Malyszko et al 19 and Takeda et al 20 explained acute water immersion restraint and acute cold -restraint stress which further causes reduced collageninduced aggregation in whole blood and ADP-induced aggregation in platelet-rich plasma, respectively. Similarly, in the present study, decreased platelet count in animals by acute restraint stress were observed.…”
Section: Discussionmentioning
confidence: 99%